Analysis of Open Channel Design at The Railway Subsidiary Location at KM 206+100 - KM 206+560 of The Tanjung Karang Divre IV Gilas Emplasement: Analisis Perencanaan Saluran Terbuka pada Lokasi Amblesan Jalur Kereta Api di KM 206+100 - KM 206+560 Emplasemen Gilas Divre IV Tanjung Karang - pranata, yogi; Henggar Risa Destania; Ghina Amalia (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Railway track subsidence at Km 206+100–Km 206+560 of the Gilas Emplacement, Divre IV Tanjung Karang, is caused by the interaction between saturated soil conditions, high groundwater levels, and an underperforming drainage system. Field investigations show that the 0–5 m soil layer is dominated by high-plasticity clay, while the 5–10 m layer consists of sandy clay, and the layer below 10 m is silty sand. Geoelectrical data indicate groundwater levels as shallow as 1.5 m below the rail head, causing soil saturation and resulting in pumping effects under dynamic train loading. This accelerates the formation of slip surfaces and decreases slope safety factors (SF < 1.5). This study evaluates drainage improvements by designing an open drainage channel system. Calculations show that the planned channel capacity is 2.6 m³/s, exceeding the runoff discharge in Area A1 (2.5 m³/s). Existing channel dimensions are also adequate to convey runoff. Additionally, subsurface drainage and vertical drain systems are required to lower groundwater levels and maintain slope stability. The recommended HDPE pipe diameter is 14 inches, adjusted to field availability.